2006
DOI: 10.1074/jbc.m512095200
|View full text |Cite
|
Sign up to set email alerts
|

The Biochemical Characterization of Ferret Carotene-9′, 10′-Monooxygenase Catalyzing Cleavage of Carotenoids in Vitro and in Vivo

Abstract: Previous studies have shown that ␤-carotene 15,15-monooxygenase catalyzes the cleavage of ␤-carotene at the central carbon 15,15-double bond but cleaves lycopene with much lower activity. However, expressing the mouse carotene 9,10-monooxygenase (CMO2) in ␤-carotene/lycopene-synthesizing and -accumulating Escherichia coli strains leads to both a color shift and formation of apo-10-carotenoids, suggesting the oxidative cleavage of both carotenoids at their 9,10-double bond. Here we provide information on the bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
258
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(268 citation statements)
references
References 31 publications
9
258
0
1
Order By: Relevance
“…These micelles are solubilized under aqueous conditions and are absorbed by intestinal cells (1)(2)(3)(4)(5)(6). Moreover, detergent micelles of -carotene have been used in the conversion of -carotene to retinal under aqueous conditions (4,10,(14)(15)(16)(17)(18)(19)(20). Thus, we investigated the effect of factors such as solvent, detergent, and substrate on the formation of detergent micelles of -carotene for retinal production under aqueous conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These micelles are solubilized under aqueous conditions and are absorbed by intestinal cells (1)(2)(3)(4)(5)(6). Moreover, detergent micelles of -carotene have been used in the conversion of -carotene to retinal under aqueous conditions (4,10,(14)(15)(16)(17)(18)(19)(20). Thus, we investigated the effect of factors such as solvent, detergent, and substrate on the formation of detergent micelles of -carotene for retinal production under aqueous conditions.…”
Section: Resultsmentioning
confidence: 99%
“…However, because these micelles were used to investigate enzyme characterization other than retinal production, only a small amount of -carotene was used (4,10,(14)(15)(16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…Both CMO I and CMO II are highly expressed in mouse and human liver [41,42]. Indeed, LYC metabolites, including apo-8′-lycopenal and apo-10′-lycopenal, are in the liver of LYC-fed rats and ferrets, respectively, suggesting LYC cleavage by CMO II [43,44]. Therefore, if PE and PF have less affinity for CMO I and II, then enzymatic and non-enzymatic cleavage of LYC in the liver would ultimately result in decreased hepatic LYC concentrations relative to PE and PF.…”
Section: Discussionmentioning
confidence: 99%
“…Thereafter, several related carotenoid-15,15Ј-oxygenases (CMO1) have been identified and characterized in vertebrates including human beings (4)(5)(6)(7). In addition, in vertebrates a second type of carotenoid-oxygenase, carotenoid-9Ј,10Ј-monooxygenase (CMO2) has been identified that cleaves carotenoids asymmetrically (8,9), although its physiological function is not yet fully understood.…”
Section: Rpe65 ͉ Vision ͉ Visual Chromophorementioning
confidence: 99%
“…Interestingly, carotenoid-oxygenases and the retinoid isomerase RPE65 belong to a family of structurally related nonheme iron oxygenases (9,14) that was first described in plants (15). Whereas mammalian genomes encode three family members (RPE65, CMO1 and CMO2), insect genomes (such as Drosophila melanogaster, Anopheles gambiae, or Apis mellifera) encode only a single member of this class of enzyme, namely NinaB.…”
Section: Rpe65 ͉ Vision ͉ Visual Chromophorementioning
confidence: 99%